Insuficiencia respiratoria aguda en paciente masculino de 59 años con antecedentes de insuficiencia renal crónica. - Moran Pabón, Kerly Elizabeth (2020)
Acute respiratory failure is a disease where the organism's respiratory system is unable to maintain gas exchange, and thus have adequate arterial oxygen and carbon dioxide levels for the demands of cellular metabolism. The present clinical case is a 59-year-old patient who was admitted with dyspnea, paleness, and cough as the main symptoms, in addition to a history of diabetes mellitus and renal failure. We must bear in mind that acute respiratory failure is not a pathology, but a complication resulting from other types of pathologies that may be affecting the body. Laboratory tests such as blood gases were the main diagnostic measures to verify or rule out other types of pulmonary affectation, as for blood gases, it presented abnormal values of arterial gases. The patient was followed up to see if there was a complete improvement due to his underlying disease.